The Role of Music in Families of Children With Hearing Loss and Normal Hearing in Australia, Finland, and the UK - Looi, Valerie; Torppa, Ritva; Prvan, Tania; Vickers, Debi (Frontiers in Neuroscience, 2019)
The primary aim of this current study was to compare the role, importance and value placed on music by families with normally hearing (NH) children, to those who had a child with a hearing loss (HL) who wore either hearing aids and/or cochlear implants. A secondary aim was to see whether this differed between three countries. Parents of children aged 2 to 6 years living in Australia, Finland, and the United Kingdom were invited to complete the Role of Music in Families Questionnaire (RMFQ). Two groups of participants were recruited from each country: i) parents of NH children, and ii) parents of children with a HL. The RMFQ had seven subsections covering topics such as music participation, attitudes to music, importance of music in the family, and future perspectives on music. 322 families of NH children, and 56 families of children with HL completed the questionnaire (Australia: 50 NH, 25 HL; Finland: 242 NH, 21 HL; UK: 30 NH, 10 HL). Analyses compared between NH and HL groups within each country, and between the three countries for the NH group, and the HL group, independently. Overall, there were few significant differences between the participation levels, role, or importance of music in families with NH children compared to those with a child who had a HL, regardless of whether the families lived in Australia, Finland or the United Kingdom. Children first started to respond to music at similar ages, and overall music participation frequency, and music enjoyment were relatively similar. The importance of music in the family was also similar between the NH and HL groups. In comparing between the countries, Finnish children had a tendency to have higher participation rates in musical activities, with few other differences noted. Overall, the results of this study indicate that children, regardless of hearing levels or country of residence, have similar levels of music engagement and enjoyment, and HL is not seen as a contraindication to music participation and involvement by the parents involved in this study.